An analysis of barriers to entry of cardiac rehabilitation in patients with diabetes: Using data from the National Audit of Cardiac Rehabilitation. (March 2018) - Harrison, Alexander S; Doherty, Patrick; Phillips, Anne
Background: UK cardiac rehabilitation has reached for the first time 50% uptake in 2016; however, this still leaves 50% of the eligible group not starting cardiac rehabilitation. The characteristics of patients missing cardiac rehabilitation are relatively unknown with some studies in America suggesting that patients with diabetes have a reduced likelihood of joining cardiac rehabilitation. Methods: This study used routinely collected data from the National Audit of Cardiac Rehabilitation to investigate proportional differences in patients with cardiovascular disease with, and without, diabetes taking up the offer of cardiac rehabilitation. Results: The proportion of patients with diabetes entering cardiac rehabilitation dropped by between 7% and 15% depending on the age group (<40 years, 7% reduction; 61–80 years, 15%). The study's results showed that in all demographic and diagnostic groups, the proportion of patients with diabetes was significantly less than that of the eligible group ( p < 0.001). There was no difference in the proportion of loss, from eligible to starting cardiac rehabilitation, between males and females, which was 13% for both groups. Conclusion: This study confirms, in a new UK population with over 121, 002 eligible patients, that there is a statistically significant drop in patients with diabetes taking up cardiac rehabilitation. This study is unique in looking at all four key diagnosis and treatment groups and comparing them to those taking up cardiac rehabilitation. To achieve the target of 65% uptake set by NHS England, improvements in identifying and targeting complex patients, such as those with diabetes, need to be adopted.